2001
DOI: 10.1042/0264-6021:3560705
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of matrix metalloproteinase-26, a novel metalloproteinase widely expressed in cancer cells of epithelial origin

Abstract: Identification of expanding roles for matrix metalloproteinases (MMPs) in complex regulatory processes of tissue remodelling has stimulated the search for genes encoding proteinases with unique functions, regulation and expression patterns. By using a novel cloning strategy, we identified three previously unknown human MMPs, i.e. MMP-21, MMP-26 and MMP-28, in comprehensive gene libraries. The present study is focused on the gene and the protein of a novel MMP, MMP-26. Our findings show that MMP-26 is specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 53 publications
2
83
0
Order By: Relevance
“…MMP-26 (endometase or matrilysin-2) is a rather novel MMP originally found in normal placenta and endometrium [17,26,29] but is also widely expressed in malignant tumors, such as endometrial, prostate, breast, and oral squamous cell cancers, and tumor cell lines [14,21,32]. We did not detect MMP-26 in melanoma cells in vivo.…”
Section: Discussionmentioning
confidence: 87%
“…MMP-26 (endometase or matrilysin-2) is a rather novel MMP originally found in normal placenta and endometrium [17,26,29] but is also widely expressed in malignant tumors, such as endometrial, prostate, breast, and oral squamous cell cancers, and tumor cell lines [14,21,32]. We did not detect MMP-26 in melanoma cells in vivo.…”
Section: Discussionmentioning
confidence: 87%
“…MMP-26 is reported to be self-activated, and cleave fibrinogen and ECM proteins (De Coignac et al, 2000;Park et al, 2000Park et al, , 2002Marchenko et al, 2001). MMP-26 can also be able to activate pro-MMP-9 (Uria and Lopez-Otin, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…It was also reported that MMP-26 was primarily expressed in epithelial cancers such as lung, breast, endometrial and prostate carcinomas and in the corresponding tumor cell lines (De Coignac et al, 2000;Park et al, 2000;Uria and Lopez-Otin, 2000;Marchenko et al, 2001;Chegini et al, 2003).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Another zinc ion and one to three calcium ions are present in the catalytic domain with a structural role. 5 All but two of the human MMPs (MMP-7 and MMP-26) have a C-terminal hemopexin-like domain, 3,6 and two MMPs (MMP-2 and MMP-9) contain fibronectin insertions into their catalytic domains. 7,8 All MMPs share a marked sequence similarity, and the similarity is maximal for the catalytic domains, where the percentage of identical residues ranges from a minimum of 33% (between MMP-21 and MMP-23) to a maximum of 86% (between MMP-3 and MMP-10).…”
Section: Introductionmentioning
confidence: 99%